2020
DOI: 10.1002/masy.201900200
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Polarity and Environment Sensitive Behavior of Coumarin Derivative

Abstract: This paper reports an investigation on ground and excited state preferential solvation index (i.e., δs2) and relative quantum yield of 2‐acetyl‐3H‐benzo[f]chromen‐3‐one (2AHBC) molecule. The title molecule shows negative values of preferential solvation index in the ground state in different binary solvent mixtures, this confirms that molecule under study is preferentially solvated by 1,4‐dioxane (DXN) rather than acetonitrile (ACN). The excited state preferential solvation index is found to be positive which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The obtained results were correlated with the literature. 40 43 It is observed that the calculated values of encounter distance ( R ) are almost double the kinetic distance ( r ) in all of the binary solvent mixtures. This demonstrates that the present work obeys the sphere of action model 44 and hence confirms the presence of static quenching reactions.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The obtained results were correlated with the literature. 40 43 It is observed that the calculated values of encounter distance ( R ) are almost double the kinetic distance ( r ) in all of the binary solvent mixtures. This demonstrates that the present work obeys the sphere of action model 44 and hence confirms the presence of static quenching reactions.…”
Section: Resultsmentioning
confidence: 95%
“…It signifies that the presence of static quenching is either due to the sphere of action model or the formation of the ground-state complex. 38 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thin films that were prepared using the spin coating technique are often affected by the solvent used. Even if the solvent used has evaporated, both the temperature and chemical properties of the solvent used will always exert an influence on the spin coated thin films [12][13][14][15][16][17] The fingerprint region is from 600 to 1400 𝑐𝑚 −1 and the functional group region is from 1400 to 4000 𝑐𝑚 −1 .…”
Section: Fourier Transform Infrared [Ftir] Resultsmentioning
confidence: 99%
“…Since last two decades, polymers are considered as an important aspect in the field of electronics, as it has proved its applicability as semiconducting material and as conducting material for devices like solar cells, transistor, light emitting diodes, actuators, and sensors. [ 1–12 ] There is a growth in interest for optical properties of organic materials. From absorption spectra, the intrinsic parameters for the materials are obtained.…”
Section: Introductionmentioning
confidence: 99%